Cu‐Promoted Sydnone Cycloadditions of Alkynes: Scope and Mechanism Studies. Issue 8 (30th December 2014) - Comas‐Barceló, Júlia; Foster, Robert S.; Fiser, Béla; Gomez‐Bengoa, Enrique; Harrity, Joseph P. A.
Abstract: Cu salts have been found to promote the cycloaddition reaction of sydnones and terminal alkynes, providing significant reduction in reaction times. Specifically, the use of Cu(OTf)2 is found to provide 1, 3‐disubstituted pyrazoles, whereas simply switching the promoter system to Cu(OAc)2 allows the corresponding 1, 4‐isomers to be produced. The mechanism of the Cu‐effect in each case has been investigated by experimental and theoretical studies, and they suggest that Cu(OTf)2 functions by Lewis acid activation of the sydnone, whereas Cu(OAc)2 promotes formation of reactive Cu I acetylides. Abstract : Vamos cobre! Cu salts promote the cycloaddition of sydnones and terminal alkynes, providing significant reduction in reaction times. Whereas Cu(OTf)2 is found to provide 1, 3‐disubstituted pyrazoles, Cu(OAc)2 allows the corresponding 1, 4‐isomers to be produced. Experimental and theoretical studies suggest that Cu(OTf)2 functions by Lewis acid activation of the sydnone, whereas Cu(OAc)2 promotes formation of reactive Cu I acetylides (see scheme; o ‐DCB=1, 2‐dichlorobenzene).